1
$\begingroup$

Let $k=(k_1,k_2) \in \mathbb{Z}^2$. Let $\lambda=(\lambda_1,\lambda_2)\in [0,2\pi]^2$ and $F(\lambda)$ be a bounded real function of $\lambda\in [0,2\pi]^2$.

I am interested in the following equation: $$ \frac{1}{(2\pi)}\int_{[0,2\pi]}\sum_{l=-\infty}^\infty \lvert l\rvert \bigg\lvert\frac{1}{2\pi}\int_{[0,2\pi]} e^{il\lambda_1 }F(\lambda)d\lambda_1 \bigg\rvert^2{d\lambda_2}\\ +\frac{1}{(2\pi)}\int_{[0,2\pi]}\sum_{l=-\infty}^\infty \lvert l\rvert \bigg\lvert\frac{1}{2\pi}\int_{[0,2\pi]} e^{il\lambda_2 }F(\lambda)d\lambda_2 \bigg\rvert^2{d\lambda_1} \\=\sum_{k\in \mathbb{Z}^2}|k_1|\bigg|\frac{1}{(2\pi)^2}\int_{[0,2\pi]^2}e^{i(k_1\lambda_1+k_2\lambda_2)}F(\lambda)d\lambda\bigg|^2\\ \\+\sum_{k\in \mathbb{Z}^2}|k_2|\bigg|\frac{1}{(2\pi)^2}\int_{[0,2\pi]^2}e^{i(k_1\lambda_1+k_2\lambda_2)}F(\lambda)d\lambda\bigg|^2 $$ Can anyone give me a brief explanation as to why the statement is wrong or give me a hint for the solution?

$\endgroup$
2
  • $\begingroup$ The solution of what? $\endgroup$
    – LSpice
    Commented Nov 2, 2021 at 23:21
  • $\begingroup$ My question is how do I get from one side of the equation to the other side of the equation? $\endgroup$
    – HyyFly
    Commented Nov 2, 2021 at 23:49

1 Answer 1

2
$\begingroup$

$\newcommand\Z{\mathbb Z}$Suppose that $F$ is a bounded measurable complex-valued function on $[0,2\pi]^2$, so that $F\in L^2([0,2\pi]^2)$. Then $$F(s,t)=\sum_{(m,n)\in\Z^2}c_{m,n}e^{i(ms+nt)} \tag{1}$$ for some complex $c_{m,n}$'s such that $\sum_{(m,n)\in\Z^2}|c_{m,n}|^2<\infty$ (the above double series converges in $L^2([0,2\pi]^2)$).

Now direct calculations (see details below) show that the left-hand side (lhs) of your identity is $\sum_{(l,n)\in\Z^2}|l|(|c_{l,n}|^2+|c_{n,l}|^2)$, whereas the right-hand side (rhs) of your identity is $\sum_{(k_1,k_2)\in\Z^2}(|k_1|+|k_2|)||c_{k_1,k_2}|^2$, which is obviously the same as the left-hand side.

Thus, your identity does hold.


Details: By (1), $$I_l:=\frac1{2\pi}\int_0^{2\pi}e^{ils}F(s,t)ds =\sum_{(m,n)\in\Z^2}c_{m,n}e^{int}1(m=l) =\sum_{n\in\Z}c_{l,n}e^{int},$$ and hence $$|I_l|^2=I_l\overline{I_l} =\sum_{(m,n)\in\Z^2}c_{l,m}\overline{c_{l,n}}e^{i(m-n)t}$$ and $$\frac1{2\pi}\int_0^{2\pi}|I_l|^2 dt =\sum_{(m,n)\in\Z^2}c_{l,m}\overline{c_{l,n}}1(m=n) =\sum_{n\in\Z}|c_{l,n}|^2.$$ So, the first summand on the lhs of your identity is $\sum_{(l,n)\in\Z^2}|l||c_{l,n}|^2$ and, similarly, the second summand there is $\sum_{(l,n)\in\Z^2}|l||c_{n,l}|^2$, so that the lhs of your identity is $\sum_{(l,n)\in\Z^2}|l|(|c_{l,n}|^2+|c_{n,l}|^2)$.

Next, again by (1), $$\frac1{(2\pi)^2}\int_{[0,2\pi]^2}e^{i(k_1s+k_2t)}F(s,t)ds\,dt \\ =\frac1{(2\pi)^2}\int_{[0,2\pi]^2}e^{i(k_1s+k_2t)}\sum_{(m,n)\in\Z^2}c_{m,n}e^{i(ms+nt)}ds\,dt \\ =\sum_{(m,n)\in\Z^2}c_{m,n}1(m=k_1,n=k_2)=c_{k_1,k_2}.$$ So, the rhs of your identity is $\sum_{(k_1,k_2)\in\Z^2}(|k_1|+|k_2|)|c_{k_1,k_2}|^2$.

$\endgroup$
1
  • 1
    $\begingroup$ @HyyFly : I have added details of the calculation. $\endgroup$ Commented Nov 3, 2021 at 15:45

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.